Inkjet-Printing of Methylammonium Lead Trihalide Perovskite as Active Layers for Optoelectronic Devices. (12th February 2018) - Trudeau, Charles; Bolduc, Martin; Beaupré, Patrick; Benavides-Guerrero, Jaime; Tremblay, Bruno; Cloutier, Sylvain G.
ABSTRACT: New routes in additive devices fabrication techniques and advances in printable materials are required to meet the ever increasing demands for low-cost and large-area flexible electronics. In particular, perovskite-based materials have gained an appeal due to their unique optoelectronics and ferroelectrics properties, which may replace p-n junction in semiconductor devices. Metal-organic methylammonium lead trihalide perovskite formulations have been extensively studied in the last few years as promising materials for use in printed electronics, which do not require high temperatures or vacuum environment, contrary to conventional semiconductor fabrication techniques. In this work, digital inkjet-printing in ambient atmosphere is proposed as a deposition pathway for the fabrication of perovskite active layers in photodetector and thin-film photovoltaic device architectures. The device architecture containing a printed perovskite active layer sandwiched between TiO2 and Spiro-OMeTAD as electron and hole transport layers, respectively, as well as layer-on-layer fabrication and responsivity spectra of the perovskite-based device are presented.